Limb dominance influences landing mechanics and neuromuscular control during drop vertical jump in patients with ACL reconstruction - Xue, Boshi; Yang, Xiaowei; Wang, Xia; Yang, Chen; Zhou, Zhipeng (Frontiers in Physiology, 2024)
The purpose of this study was to compare the interlimb biomechanical differences in patients who had undergone anterior cruciate ligament reconstruction (ACLR) in either dominant (ACLR-D) or nondominant (ACLR-ND) limbs and healthy controls (CON) during drop vertical jump (DVJ) task. To investigate whether the dominant or nondominant limb influences the risk of re-injury in ACLR patients.Methods: Thirty-three ACLR patients were divided into ACLR-D and ACLR-ND groups according to whether the surgical limb was dominant or nondominant. Seventeen healthy individuals were selected as the CON group. Three-dimensional kinematic data, ground reaction force (GRF) data, and surface electromyographic (EMG) data from the bilateral lower limbs of all participants were collected during the DVJ task. Two-way repeated-measures ANOVAs (limb × group) were performed on the variables of interest to examine the main effects of limb (dominant vs. nondominant) and group (ACLR-D, ACLR-ND, and CON), as well as the interaction between limb and group.The nonsurgical limbs of ACLR group had significantly greater knee valgus angles, knee extension and valgus moments, peak posterior GRF (PPGRF), and peak vertical GRF (PVGRF) compared to the surgical limbs. The nonsurgical limbs of ACLR-ND patients demonstrated significantly greater knee extension and valgus moments, greater PPGRF and PVGRF, and reduced muscle activity in the vastus medialis and vastus lateralis compared to the CON group. The ACLR patients had reduced muscle activity in the quadriceps of the surgical limb and the hamstrings of the bilateral limbs compared to controls.The nonsurgical limbs of ACLR patients may suffer an increased risk of ACL injury due to altered landing mechanics and neuromuscular control strategies compared to the surgical limbs. Additionally, limb dominance influences movement patterns and neuromuscular control during DVJ task, the nonsurgical limbs of the ACLR-ND might be at higher risk of ACL injury compared to the ACLR-D group.